Advancements in Noninvasive Volatile Organic Compound Detection: Integrating Stirling Cooling Preconcentration with GC-FID/MS for Quantitative Breath Analysis - Xu, Qiongdan; Hu, Xiaoyu; Zhong, Lei; Wang, Zelin; Zhao, Huayong; Fu, Jia; Cao, Dongdong; Liu, Liu; Zhang, Yan; Lang, Jianlei (ACS omega, 2025)
The study of volatile organic compounds (VOCs) in exhaled breath presents significant potential for noninvasive disease diagnosis and human exposure monitoring. While thermal desorption (TD) tubes are the most commonly used preconcentration technique for analyzing VOCs in breath, they still face practical challenges, mainly selective adsorption and interference from water vapor in breath samples. This study is the first to develop a method combining Stirling cooling preconcentration technology with gas chromatography-flame ionization detector/mass spectrometry (GC-FID/MS) and a SUMMA canister, enabling simultaneous detection of 116 VOCs. The method requires no refrigerants and effectively addresses the selective adsorption and water vapor interference issues found with TD tubes. Furthermore, nitrogen pressurization is used to dilute the original gas, and calibration curves encompassing various linear ranges are developed to quantify the targeted VOCs across different concentration levels. Finally, we analyzed exhaled breath samples from eight healthy subjects and validated the method. The results showed that the coefficients of determination (R 2) for the linear equations of all target compounds exceeded 0.998, with limits of detection and quantification (LOQ) ranging from 0.01 to 0.09 ppbv and 0.03 to 0.35 ppbv, respectively, and precision within 20%. Accuracy, except for a few substances, was generally between 70% and 130%. This study offers robust technical support for the accurate quantification of VOCs at various concentration levels in exhaled breath.